1985
DOI: 10.1126/science.227.4684.292
|View full text |Cite
|
Sign up to set email alerts
|

Subtropical Atlantic Climate Studies: Introduction

Abstract: This report is an introduction to the accompanying collection of reports that present the results of a 2-year period of intensive monitoring of the Florida Current. Both direct observing systems (ship-deployed current profilers and moored current meters) and indirect observing systems (coastal tide gauge stations, bottom pressure gauge arrays, a submarine cable, acoustic arrays, and radar installations) were used to measure temperature and volume transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 14 publications
0
17
2
Order By: Relevance
“…An intensive study of the Florida Current made during the STACS program by a variety of measuring techniques had provided some information on the structure of variability in the Florida Straits (e.g. Molinari et al, 1985;Leaman et al, 1987;Schott et al, 1988), however the relatively short time scale of the STACS observations (a few years) made it 854 C. P. Atkinson et al: Atlantic transport variability at 26 • N difficult to resolve variability on the sub-annual to interannual periods of interest here.…”
Section: Emergence Of the Florida Straits Seasonal Transport Cycle Frmentioning
confidence: 99%
See 1 more Smart Citation
“…An intensive study of the Florida Current made during the STACS program by a variety of measuring techniques had provided some information on the structure of variability in the Florida Straits (e.g. Molinari et al, 1985;Leaman et al, 1987;Schott et al, 1988), however the relatively short time scale of the STACS observations (a few years) made it 854 C. P. Atkinson et al: Atlantic transport variability at 26 • N difficult to resolve variability on the sub-annual to interannual periods of interest here.…”
Section: Emergence Of the Florida Straits Seasonal Transport Cycle Frmentioning
confidence: 99%
“…Mass transport through the Florida Straits has been almost continuously measured since April 1982 using a succession of submerged telephone cables located between 26 • N-27 • N (Larsen, 1992;Baringer and Larsen, 2001;Meinen et al, 2010). These observations began during the Sub Tropical Atlantic Climate Studies (STACS) program which ran from 1982-1984 and used a variety of measurement techniques to study the Florida Current (Molinari et al, 1985). Amongst many other results, STACS revealed that Florida Straits transport variability has a near continuous power spectrum and an apparent asymmetric seasonal cycle with a range of several Sverdrups.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The Subtropical Atlantic Climate Studies program (STACS) [Molinari et al, 1985a] involved repeated sections across the Florida Current between 1982 and 1984. Vertical profiles of velocity and temperature were obtained using the free-falling acoustically tracked ''Pegasus'' profiler at 9 stations (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The Subtropical Atlantic Climate Studies (STACS) Program of the National Oceanic and Atmospheric Administration (NOAA) is directed at increased understanding of the dynamics of the circulation of the subtropical North Atlantic and the role this circulation plays in modifying global atmospheric climate, as well as the development of sampling strategies to monitor operationally the climatically important oceanic phenomena [Molinari, 1986]. Initially, STACS efforts were directed at the Florida Current at 27øN [Molinari et al, 1985;Molinari, 1986]. A submarine communications cable is now being used operationally to monitor Florida Current transport [Larsen, 1987].…”
Section: Introductionmentioning
confidence: 99%